Public art in waterfronts: pretext and recontext - Ochoa, R. (On the W@terfront, 2008)
Urban waterfronts, because of their potentialities – representation, symbolic, poetical… –, constitute propitious places to the existence of public art. Nevertheless, the waterfront’s urban landscape harnesses other approaches to public art that can be diverse from the production of author works or of artistic events. In a more including position, we can consider some presences that, although having not be intentionally produced to be public art, consists as such, therefore had earned, in an ampler direction, proper meanings, because of their symbolic charge, as well of their influence in the proper profile of the city. Elements like the gasometers of Matinha’s Gas Factory or even the presence of the Portico of Lisnave (which is already classified as public art) could be re-contextualized. It can be done, for example, in the scope of artistic itineraries, focused in spreading the industrial and port heritage of the city. On their condition of public art, these elements, translating place’s specificities, establishing themselves as identity factors, are susceptible to create new urban living experiences and to work as a motor of knowledge of the city and its history, using as a unifying support one of its main container axes: the waterfront.